2017
DOI: 10.1016/j.shaw.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Styrene Exposure on Auditory Function Among Adults: A Systematic Review of Selected Workers

Abstract: A review study was conducted to examine the adverse effects of styrene, styrene mixtures, or styrene and/or styrene mixtures and noise on the auditory system in humans employed in occupational settings. The search included peer-reviewed articles published in English language involving human volunteers spanning a 25-year period (1990–2015). Studies included peer review journals, case–control studies, and case reports. Animal studies were excluded. An initial search identified 40 studies. After screening for inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…This variability is attributed to several factors other than these included in the ISO model, such as coexposure to ototoxic substances (organic solvents, ototoxic drugs), heredity (gene polymorphisms), and several determinants of individual susceptibility to noise, such as an increased level of lipids, metabolic diseases (diabetes), hypertension, as well as habits (cigarette smoking) [30]. The results of recent systematic review papers call for an urgent implementation of hearing protection standards for workers exposed to organic solvents, such as styrene, toluene and mixtures of solvents, particularly in the case of combined exposures to these chemicals and noise [31,32]. As a consequence of studies on organic solvents, the updated European Directive 2003/10/EC [33] stipulates that employers should estimate the risk of hearing impairment due to exposure to organic solvents in co-exposure with noise.…”
Section: Prevention Of Occupational Nihl By Monitoring Tts Incidents?mentioning
confidence: 99%
“…This variability is attributed to several factors other than these included in the ISO model, such as coexposure to ototoxic substances (organic solvents, ototoxic drugs), heredity (gene polymorphisms), and several determinants of individual susceptibility to noise, such as an increased level of lipids, metabolic diseases (diabetes), hypertension, as well as habits (cigarette smoking) [30]. The results of recent systematic review papers call for an urgent implementation of hearing protection standards for workers exposed to organic solvents, such as styrene, toluene and mixtures of solvents, particularly in the case of combined exposures to these chemicals and noise [31,32]. As a consequence of studies on organic solvents, the updated European Directive 2003/10/EC [33] stipulates that employers should estimate the risk of hearing impairment due to exposure to organic solvents in co-exposure with noise.…”
Section: Prevention Of Occupational Nihl By Monitoring Tts Incidents?mentioning
confidence: 99%
“…More recently, a weight-of-evidence-based review of animal and human epidemiological evidence for ototoxicity of styrene concluded that, although the human data were less clear than animal data in terms of establishing a doseresponse relationship, the overall evidence favors the conclusion that styrene is ototoxic (Vyskocil et al 2012). Similarly, while recognizing the complications imposed by multiple confounding factors (including exposure to noise and/or other chemicals as well as age and sex) a 2017 systematic review recommended that chronic styreneexposed workers be routinely evaluated with a comprehensive audiological test battery to identify early signs of hearing impairment (Pleban, Oketope, and Shrestha 2017).…”
Section: Non-cancer Health Effectsmentioning
confidence: 99%
“…Meanwhile, noise exposure can damage the human cardiovascular system, autonomic nervous system, endocrine system, and neurocognitive functioning [ 9 ]. Extreme environmental temperatures significantly increase the risks of cardiovascular diseases [ 10 ], neurodegenerative diseases [ 11 ], depression [ 12 ], and anxiety [ 13 ]. In addition, illumination and light can impact human cognitive functions [ 14 ].…”
Section: Introductionmentioning
confidence: 99%